Investigation of Star Fruit (Averrhoa Carambola) Juice Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Star fruit (Averrhoa carambola) is widely grown in Vietnam. It is a good source of natural antioxidants especially proanthocyanidins, epicatechin and vitamin C. It is quite a popular fruit usually consumed fresh or made into fruit juice or juice beverage. In order to utilize this good source as a healthy food drink, we attempted to produce star fruit juice. We focused on investigation of dilution ratio of star fruit juice with water, soluble dry matter, and pasteurization to product quality. Our results showed that dilution ratio 40:60 (juice: water), 20 oBrix, pasteurization at 90 oC in 5 minutes gave the best star fruit juice.Keywords: Star fruit, Averrhoa carambola, Juice, Pasteurization, Soluble dry matter, dilution ratio.